Peran LLP RRI Padang Dalam Memberikan Informasi Kepada Masyarakat Sumatera Barat - Andika, Jefri; Habibi, Muhammad; Syafril, Rizki (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2024)
This research is entitled Determining Factors of Millennial Generation Interest in Investing in Sharia Stocks using the Theory of Planned Behavior Approach. The aim of this research is to determine the influence of attitudes, subjective norms, and perceived behavioral control on interest in sharia stock investment, both partially and simultaneously. This research uses a quantitative approach, the data collection method used is a questionnaire. The population in this study was the millennial generation in Ajjalireng Village, Sijelling Village, Waji Village, and Patangnga Village. Meanwhile, the number of samples used was 100 samples. The data that has been collected will go through the stages of validity testing, reliability testing, classical assumption testing, and hypothesis testing. Data processing was carried out with the help of the SPSS version 25 analysis tool. The results of the study showed that attitudes had a positive and significant effect on interest in sharia stock investment, subjective norms had no effect on interest in sharia stock investment, perceived behavioral control had a positive and significant effect on interest in sharia stock investment.